On the low-frequency relationship between public deficits and inflation - Alexander Kriwoluzky; Martin Kliem; Samad Sarferaz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We estimate the low-frequency relationship between fiscal deficits and inflation and pay special attention to its potential time variation by estimating a time-varying VAR model for U.S. data from 1900 to 2011. We find the strongest relationship neither in times of crisis nor in times of high public deficits, but from the mid-1960s up to 1980. Our results suggest that the low-frequency relationship between fiscal deficits and inflation is strongly related to the conduct of monetary policy and its interaction with fiscal policy after World War II.
Keywords: E42; E58; E61; 330